Pragmatic randomised controlled trial of very early etanercept and MTX versus MTX with delayed etanercept in RA: the VEDERA trial. Issue 4 (29th January 2020) - Emery, Paul; Horton, Sarah; Dumitru, Raluca Bianca; Naraghi, Kamran; van der Heijde, Désirée; Wakefield, Richard J; Hensor, Elizabeth M A; Buch, Maya H
Abstract : Objectives: We sought to confirm in very early rheumatoid arthritis (ERA) a much greater superiority (30%) of first-line etanercept+methotrexate (ETN+MTX) over treat-to-target MTX (MTX-TT) than previously reported in ERA (14%); and explore whether ETN following initial MTX secures a comparable response to first-line ETN+MTX. Methods: Pragmatic, open-label, randomised controlled trial of treatment-naïve ERA (≤12 months symptom), Disease Activity Score 28 joint (DAS28)-erythrocyte sedimentation rate (ESR) ≥3.2, rheumatoid factor (RF)+/−anticitrullinated peptide antibody (ACPA) positive or ultrasound power Doppler (PD) if RF and ACPA negative. Subjects were randomised 1:1 to ETN+MTX; or MTX-TT, escalated to ETN if week 24 DAS28-ESR ≥2.6 and intramuscular corticosteroid at protocolised time points. Primary endpoint of week 48 DAS28ESR remission with clinical and imaging secondary endpoints. Results: We randomised 120 patients, 60 to each arm (71% female, 73% RF/84% ACPA positive, median (IQR) symptom duration 20.3 (13.1, 30.8) weeks; mean (SD) DAS28 5.1 (1.1)). Remission rates with ETN+MTX and MTX-TT, respectively, were 38% vs 33% at week 24; 52% vs 38% at week 48 (ORs 1.6, 95% CI 0.8 to 3.5, p=0.211). Greater, sustained DAS28-ESR remission observed with ETN+MTX versus MTX-TT (42% and 27%, respectively; p=0.035). PD was fully suppressed by week 48 in over 90% in each arm. Planned exploratory analysis revealed OR 2.84, 95% CI 0.8 to 9.6) of achieving remission after 24 weeks of ETN administered first line compared with administered post-MTX. Conclusions: Compared with remission rates typically reported with first-line tumour necrosis factor inhabitor+MTX versus MTX-TT, we did not demonstrate a larger effect in very ERA. Neither strategy conferred remission in the majority of patients although ultrasound confirmed local inflammation suppression. Poorer ETN response following failure of MTX-TT is also suggested. Trial registration number NCT02433184